2022
DOI: 10.1002/mc.23446
|View full text |Cite
|
Sign up to set email alerts
|

The transglutaminase 2 cancer cell survival factor maintains mTOR activity to drive an aggressive cancer phenotype

Abstract: Transglutaminase 2 (TG2) is an important cancer stem-like cell survival protein that is highly expressed in epidermal squamous cell carcinoma and drives an aggressive cancer phenotype. In the present study, we show that TG2 knockdown or inactivation results in a reduction in mammalian target of rapamycin (mTOR) level and activity in epidermal cancer stem-like cells which are associated with reduced spheroid formation, invasion, and migration, and reduced cancer stem cell and epithelial-mesenchymal transition (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The two‐tailed the Student's t test was used for binary comparison between control and experimental groups. All experiments were repeated three times and the data is presented as mean ± SEM 32 …”
Section: Methodsmentioning
confidence: 99%
“…The two‐tailed the Student's t test was used for binary comparison between control and experimental groups. All experiments were repeated three times and the data is presented as mean ± SEM 32 …”
Section: Methodsmentioning
confidence: 99%
“…Although TG2 is well-known for its function in the maintenance of CSC-like cell survival in diverse cancers such as breast cancer [ 38 ], epidermal squamous cell carcinoma [ 39 ], renal cell carcinoma [ 40 ], ovarian cancer [ 41 ], and colon cancer [ 42 ], little is known about its role in liver CSCs [ 43 ]. In contrast, two independent clinical studies showed that the tissue and/or serum TG2 expression were significantly increased in patients with early stage HCC whose with no evaluated level of AFP [ 44 ] or with early recurrence within 12 months after primary treatment [ 45 ].…”
Section: Introductionmentioning
confidence: 99%